Thermal enhancement of gas transfer velocity of CO2 in an Amazon floodplain lake revealed by eddy covariance measurements. Issue 9 (15th May 2013) - Polsenaere, Pierre; Deborde, Jonathan; Detandt, Guillaume; Vidal, Luciana O.; Pérez, Marcela A. P.; Marieu, Vincent; Abril, Gwenaël
Abstract : [1] In November 2011, the partial pressures of carbon dioxide (pCO2 ) in water and air in a floodplain lake of the Amazon River in Brazil were 800 ± 75 and 387 ± 8 ppmv, respectively. Turbulent CO2 fluxes from the lake measured with eddy covariance ranged from 0.05 to 2.2 µmol m −2 s −1 . The corresponding gas transfer velocities k 600 ranged from 1.3 to 31.6 cm h −1, averaging 12.2 ± 6.7 cm h −1 . At moderate to high wind speed, k 600 increased with wind speed, with values above parameterizations for other lake ecosystems. During the prevailing tropical low wind speed (below 2.7 m s −1 ) and high insolation conditions, unexpected high k 600 values (up to 20 cm h −1 ) were obtained and correlated with latent heat and sensible heat fluxes. In Amazonian open lakes, owing to long quiescent periods of low wind speed but extremely high daytime insolation and heat fluxes, thermal enhancement makes time‐integrated gas transfer velocities four to five times higher than those computed from classic wind parameterization. Key Points: First eddy covariance measurements Gas exchange is enhanced CO2 outgassing from floodplain lakes is larger